Utilizing Qual2Kw software to calculate the pollution load capacity of Ciliwung River Segment IV (Depok City) - Prianggono, Margahayu; Rosadi, Rosadi; Sutanto, Sutanto (Indonesian Journal of Applied Environmental Studies, 2024)
Situated in the administrative boundaries of West Java Province and DKI Jakarta Province, the Ciliwung River is a national river. Its river length is about 120 km, and its watershed area is about 425 km³ (DAS). The population of Depok City is growing at a pace of 1.79% annually, which leads to a rise in the demand for food, clothing, and housing, among other necessities. As a result of the growth of various industrial and community residential buildings to accommodate human needs, wastewater discharge into rivers will increase and the amount of pollution entering the Ciliwung River may surpass its carrying capacity if efforts are not made to control water pollution. As a result, research must be done to ascertain Segment IV Depok City's Ciliwung River Pollutant Load Capacity utilizing a simulation model and Qual2Kw software. Primary data samples of the Ciliwung River's water and pollution sources that enter it were collected for this study, in addition to firsthand field observations. Data calibration is carried out after entering hydraulic and quality data into worksheets. In order to ensure that river flow data still satisfies class II river water quality standards, modeling is done utilizing the following sources: (1) existing data; (2) upstream data of class II river water quality standards; and (3) current conditions of river flow and trial & error pollutant source data. The findings indicated that the Ciliwung River section IV, Depok City, has a somewhat contaminated water quality. Pollutant loads for TSS and COD criteria can still be accommodated in Ciliwung River section IV, Depok City. In the meantime, the BOD criteria for carrying pollutant loads has been surpassed; therefore, to meet class II water quality regulations, the BOD pollutant load needs to be reduced by 22.58% to 37.50%. ABSTRAK Terletak di batas administratif Provinsi Jawa Barat dan Provinsi DKI Jakarta, Sungai Ciliwung merupakan sungai nasional. Panjang sungainya sekitar 120 km, dan luas daerah aliran sungainya sekitar 425 km³ (DAS). Pertumbuhan penduduk Kota Depok sebesar 1,79% setiap tahunnya menyebabkan peningkatan permintaan terhadap pangan, sandang, papan, dan kebutuhan lainnya. Akibat tumbuhnya berbagai bangunan industri dan pemukiman masyarakat untuk menampung kebutuhan manusia, pembuangan air limbah ke sungai akan semakin meningkat dan jumlah pencemaran yang masuk ke Sungai Ciliwung dapat melampaui daya dukungnya apabila tidak dilakukan upaya pengendalian pencemaran air. Oleh karena itu, perlu dilakukan penelitian untuk memastikan Kapasitas Beban Pencemar Sungai Ciliwung Segmen IV Kota Depok dengan menggunakan model simulasi dan software Qual2Kw. Sampel data primer air Sungai Ciliwung dan sumber pencemaran yang masuk ke dalamnya dikumpulkan untuk penelitian ini, selain observasi lapangan secara langsung. Kalibrasi data dilakukan setelah memasukkan data hidrolik dan kualitas ke dalam lembar kerja. Untuk memastikan data debit sungai masih memenuhi baku mutu air sungai kelas II, pemodelan dilakukan dengan menggunakan sumber-sumber sebagai berikut: (1) data eksisting; (2) data hulu baku mutu air sungai kelas II; dan (3) kondisi aliran sungai terkini dan data sumber pencemar trial & error. Temuan menunjukkan bahwa Sungai Ciliwung seksi IV Kota Depok memiliki kualitas air yang agak tercemar. Beban pencemar kriteria TSS dan COD masih dapat tertampung di Sungai Ciliwung seksi IV Kota Depok. Sementara itu, kriteria BOD untuk memikul beban polutan telah terlampaui; Oleh karena itu, untuk memenuhi ketentuan mutu air kelas II maka beban pencemar BOD perlu diturunkan sebesar 22,58% menjadi 37,50%.